Potret Multikulturalisme dalam Novel Ranah 3 Warna Karya Ahmad Fuadi - Yunas, Naufal Zakky; Hayati, Yenni (Universitas Negeri Padang, 2024)
The purpose of this research is to find out the values and types of multiculturalism contained in the novel Ranah 3 Warna created by Ahmad Fuadi, and the influence of multiculturalism on the community groups depicted in the novel Ranah 3 Warna. This research uses the theory of literary sociology and the descriptive method. The data source for this research is the novel Ranah 3 Warna. The steps in collecting data include reading and understanding the contents of the novel, conducting literature studies related to the research problem, identifying the main and additional characters, and inventorying data related to multiculturalism in the novel. The validation technique used is the triangulation technique. The data analysis techniques involve identifying and classifying data based on the speech or actions of the characters, analyzing and interpreting the data, and drawing conclusions. The results of this research include four multicultural values - tolerance, democratic, religious, and cultural - and five types of multiculturalism - isolationist, accommodative, autonomous, critical or interactive, and cosmopolitan. The influence of multiculturalism on community groups is divided into positive and negative influence.